2008
DOI: 10.1007/bf03194279
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of heterochromatin in six species ofCtenomys (Rodentia: Octodontoidea: Ctenomyidae) from Argentina revealed by a combined analysis of C- and RE-banding

Abstract: 2008. Heterogeneity of heterochromatin in six species of Ctenomys (Rodentia: Octodontoidea: Ctenomyidae) from Argentina revealed by a combined analysis of C-and RE-banding. Acta Theriologica 53: 57-71.Exceptional chromosomal variability makes Ctenomys an excellent model for evolutionary cytogenetic analysis. Six species belonging to three evolutionary lineages were studied by means of restriction endonuclease and C-chromosome banding. The resulting banding patterns were used for comparative analysis of heteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Hypotheses concerning the function of heterochromatin remain speculative at best, but many studies with these rodents suggest a meaningful role of heterochromatin in the organization and evolution of chromosomes, in gene expression and in the expression of euchromatic DNA (Reig et al 1992;Cook and Salazar-Bravo 2004;Ipucha et al 2008). Freitas (1994) suggested that heterochromatin participates in the process of addition or deletion of chromosome arms, while Ipucha et al (2008) proposed that the heterochromatin amplification occur independently of chromosomal change in diploid number and the splitting of Ctenomys lineages is accompanied by divergence in heterochromatin composition. Moreover, Cook and Salazar-Bravo (2004) showed that Ctenomys species present a correspondence between the pattern of heterochromatic variation and phylogeny.…”
Section: Heterochromatinmentioning
confidence: 99%
“…Hypotheses concerning the function of heterochromatin remain speculative at best, but many studies with these rodents suggest a meaningful role of heterochromatin in the organization and evolution of chromosomes, in gene expression and in the expression of euchromatic DNA (Reig et al 1992;Cook and Salazar-Bravo 2004;Ipucha et al 2008). Freitas (1994) suggested that heterochromatin participates in the process of addition or deletion of chromosome arms, while Ipucha et al (2008) proposed that the heterochromatin amplification occur independently of chromosomal change in diploid number and the splitting of Ctenomys lineages is accompanied by divergence in heterochromatin composition. Moreover, Cook and Salazar-Bravo (2004) showed that Ctenomys species present a correspondence between the pattern of heterochromatic variation and phylogeny.…”
Section: Heterochromatinmentioning
confidence: 99%